Salvage radical prostatectomy in nonmetastatic castration resistant prostate cancer - López Fontana, Gastón (2022)
Objective: To analyze the perioperatory and short-oncological outcomes in 5 cases with CRPC M0 developed after pRT that underwent salvage laparoscopic RP (sLRP) and review the current evidence. Material and Methods: Perioperatory and oncological outcomes were prospectively analyzed. Inclusion criteria were patients that had received pRT and posteriorly presented with CRPC M0 in standard imagines and positron emission tomography MRI coline. Evidence was reviewed in PUBMED database. Results: No surgical complications and blood transfusion were reported. Two patients required an endoscopic urethrotomy due to bladder neck contracture (Clavien IIIb). Final pathological findings were T3 or more, multifocal with 3 positive surgical margins. Four patients reach undetectable PSA after surgery except one that continuous under ADT without disease progression. After 12 months follow-up, 4 patients persist with undetectable PSA and one with stable disease under ADT. Current evidence demonstrated that CRPC M0 treated with open, laparoscopic or robotic RP a biochemical recurrence of 68.7% as a hormonesensitive PC; however, 17.4% were disease-free after 4 years of follow-up. Conclusion: Our serie, 4 cases are disease free after 12 months follow-up. Current evidence is a retrospective and multicenter experience with few cases and intermediate oncological follow-up. More cases with longer follow-up and better evidence are required to opt for this treatment as a first line.